The Effect of A Product’s Branding on Consumer Behavior: Nivea - Erika Felicia; Margaret William Ramli; Celline Lau; Sabrina Jolyn Sukandi; Priska Basariana Panggabean (CV. Ulil Albab Corp, 2024)
This analysis focuses on the effects of a product’s branding on consumers’ behaviors. To emphasize the discussion of the branding aspect of this analysis, the subject chosen for this research is NIVEA. The subject of focus on this report is especially on how NIVEA’s branding of the company itself alongside their products influences the behavior of the public, potential consumers and already loyal product users.